Patients upgraded to cardiac resynchronization therapy due to pacing-induced cardiomyopathy are at low risk of life-threatening ventricular arrhythmias: a long-term cause-of-death analysis. Issue 1 (22nd December 2016) - Barra, Sergio; Duehmke, Rudolf; Providencia, Rui; Marijon, Eloi; Boveda, Serge; Virdee, Munmohan; Heck, Patrick; Fynn, Simon; Begley, David; Grace, Andrew; Agarwal, Sharad
Abstract: Aims: Upgrade to cardiac resynchronization therapy (CRT) should be offered to patients who have developed pacing-induced cardiomyopathy with conventional right ventricular pacing. The extent to which these patients would also benefit from defibrillator back-up at the time of CRT upgrade is, however, unknown. Methods and results: Retrospective observational cohort study of 199 patients with pacing-induced cardiomyopathy and no history of sustained ventricular arrhythmia, including 104 upgraded to CRT-Pacemaker (CRT-P) and 95 upgraded to CRT-Defibrillator (CRT-D). The incidence of ventricular arrhythmias and the risk of sudden arrhythmic death obtained through a cause-of-death analysis based on clinical data and necropsy results were assessed and compared between the two groups. During a mean follow-up of 66 ± 24 months, 40 (38.5%) CRT-P patients died: three from primary arrhythmic death, while the remaining died of different causes (especially progressive heart failure), giving an incidence of 6.2 sudden arrhythmic deaths per 1000 patient-years. No episode of sustained VT was observed in the study group. There were no sudden arrhythmic deaths in the CRT-D group during a shorter follow-up, but the small and non-significant difference in all-cause mortality between CRT-Pacemaker (CRT-P) and CRT-D groups was mostly accounted for by an increase in non-sudden death. Women upgraded to CRT were at particularly low risk of all-cause mortality compared with men (HR 0.232, P  = 0.048). Conclusion: Our findings suggest that patients who develop pacing-induced cardiomyopathy and are upgraded to CRT may not derive any significant benefit from the addition of the defibrillator in the absence of a history of ventricular arrhythmias.